2016
DOI: 10.1186/s12870-016-0773-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and expression profiling of glyoxalase gene families in soybean (Glycine max) indicate their development and abiotic stress specific response

Abstract: BackgroundGlyoxalase pathway consists of two enzymes, glyoxalase I (GLYI) and glyoxalase II (GLYII) which detoxifies a highly cytotoxic metabolite methylglyoxal (MG) to its non-toxic form. MG may form advanced glycation end products with various cellular macro-molecules such as proteins, DNA and RNA; that ultimately lead to their inactivation. Role of glyoxalase enzymes has been extensively investigated in various plant species which showed their crucial role in salinity, drought and heavy metal stress toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(124 citation statements)
references
References 61 publications
10
111
3
Order By: Relevance
“…In G. max , out of the 13 possible active GLYIs, five are predicted to be chloroplastic and four code for cytosolic proteins. In addition, the authors predict three GLYI enzymes to be nucleus-localized [30]. In agreement, as we have reported in our recent studies, the characterization of nuclear localized GLYI proteins from both rice and Arabidopsis [15].…”
Section: Subcellular Localization Properties Of Glyoxalasessupporting
confidence: 90%
See 1 more Smart Citation
“…In G. max , out of the 13 possible active GLYIs, five are predicted to be chloroplastic and four code for cytosolic proteins. In addition, the authors predict three GLYI enzymes to be nucleus-localized [30]. In agreement, as we have reported in our recent studies, the characterization of nuclear localized GLYI proteins from both rice and Arabidopsis [15].…”
Section: Subcellular Localization Properties Of Glyoxalasessupporting
confidence: 90%
“…The genome studies further revealed that among the multiple GLYI present in rice and Arabidopsis , it is the Ni 2+ -dependent form that is coded for by multiple genes, while only single gene codes for Zn 2+ -dependent GLYI [26,29]. Recently, a genome-wide study carried out in Glycine max further confirms the presence of glyoxalases as multi-gene family in plants, with G. max genome possessing 24 GLYI and 12 GLYII genes, of which three genes possibly code for Zn 2+ -dependent GLYI and eight code for Ni 2+ -dependent forms [30]. The presence of multiple Zn 2+ -dependent forms in G. max is probably the result of whole-genome duplication events in G. max .…”
Section: Presence Of Glyoxalase Isoforms In Biological Systemsmentioning
confidence: 99%
“…Recently, highthroughput RNA sequencing (RNA-seq) technology has been widely used for gene expression studies in a variety of applications, such as expression profiling of mRNAs or non-coding RNA [1][2][3], de novo assembly and characterization of transcriptomes [4,5], and the identification of novel alternatively spliced transcript [6,7]. These novel transcripts or differentially expressed genes (DEGs) identified from RNA-seq data may serve as human disease biomarkers or gene signatures for the clinical diagnosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We set m = 10,000, 1 Then, we calculated the sample size by substituting * and power into the equations (15)(16)(17)(18) and the published method using the exact test. For each designed setting, we also conducted 5000 simulations from an independent negative binomial distribution.…”
Section: Sample Size Calculation Based On Testing Multiple Genes Via mentioning
confidence: 99%
“…Recently, high-throughput RNA sequencing (RNAseq) technology has been widely used for gene expression studies in a variety of applications, such as expression profiling of mRNAs or non-coding RNA [1][2][3], de novo assembly and characterization of transcriptomes [4,5], and the identification of novel alternatively spliced transcripts [6,7]. These novel transcripts or differentially expressed genes (DEGs) identified from RNA-seq data may serve as human disease biomarkers or gene signatures for the clinical diagnosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%